How CCAFS can Help National Research Organizations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Sepo Hachigonta, Climate Modeller from University of Cape Town. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya